Ultraviolet C Decontamination Devices in a Hospital Pharmacy: An Evaluation of Their Contribution - Clara Baudart; Thomas Briot (Pharmacy)
Purpose: The COVID-19 pandemic led to a major interest in ultraviolet C (UVC) disinfection devices and accelerated the implementation of UVC devices in healthcare facilities due to their proven efficacy in the inactivation of various pathogens. While UVC technology offers several advantages, some drawbacks remain. This report, drawing on studies, guidelines, and practical experiences related to the use of UVC technology in healthcare settings, examines the efficacy, advantages, and drawbacks of UVC devices, and their applications in aseptic drug-compounding pharmaceutical units. Summary: Studies, guidelines, and practical experiences were selected. UVC technology offers advantages such as rapid disinfection, reduced reliance on chemical agents, minimal waste, and freedom from manual disinfection variability, making it particularly valuable for maintaining aseptic conditions in compounding environments. However, some drawbacks persist, as it is a germ-dependent method and there is currently no standardized method for ensuring effectiveness. Conclusions: This opinion paper highlights the effectiveness of UCV technology in pharmaceutical compounding units, proving that it is a viable alternative to the traditionally used manual and operator-dependent methods. However, there is a need for standardized methods to evaluate UVC devices.